2021
DOI: 10.1017/s0033291721002531
|View full text |Cite
|
Sign up to set email alerts
|

LSD, madness and healing: Mystical experiences as possible link between psychosis model and therapy model

Abstract: Background For a century, psychedelics have been investigated as models of psychosis for demonstrating phenomenological similarities with psychotic experiences and as therapeutic models for treating depression, anxiety, and substance use disorders. This study sought to explore this paradoxical relationship connecting key parameters of the psychotic experience, psychotherapy, and psychedelic experience. Methods In a randomized, double-blind, placebo-controlled, crossover design, 24 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 136 publications
4
46
1
Order By: Relevance
“…There are some potential limitations with our CEQ scale, as two items on the Insanity subscale were missing due to experimenter error. However, we observed good internal reliability for this scale, and our overall mean CEQ score and the Insanity subscale scores (for first and most recent experience) were similar to those observed in previous studies [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…There are some potential limitations with our CEQ scale, as two items on the Insanity subscale were missing due to experimenter error. However, we observed good internal reliability for this scale, and our overall mean CEQ score and the Insanity subscale scores (for first and most recent experience) were similar to those observed in previous studies [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, a more recent study using an orally administered dose of LSD (50 μg) also found that LSD increases suggestibility. This was not correlated with other effects such as aberrant salience processing (Wießner et al, 2021). Another study (Duerler et al, 2020) found that LSD (100 μg administered orally) increased adaptation in response to social feedback but only when opinions were not too different from the participant's own.…”
Section: Serotonergic Psychedelics and Social Influence Processingmentioning
confidence: 89%
“…Drawings under LSD showed unchanged colour quantity but increased colour abstractness , similar to previous observations on sharpened colours and changed colour combinations in drawings and paintings (Dobkin De Rios and Janiger, 2003; Tonini and Montanari, 1955). This might be related to psychedelic-induced visual effects (Kometer and Vollenweider, 2016; Wießner et al, 2021b), implying that subjective experiences might have been expressed by figural techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These contrasting relationships suggest that symbolic thinking and ambiguity constitute a third phenomenon of increased ‘meaning’, differentially related to ‘pattern break’ and decreased ‘organization’. Meaning attribution under psychedelics is widely reported but poorly understood, being associated with psychedelic-induced symbolization, mystical experiences, creativity, psychotic-like and therapeutic effects (Hartogsohn, 2018; Leptourgos et al, 2020; Liechti et al, 2017; Masters and El Houston, 1966; Preller et al, 2017; Wießner et al, 2021b), pointing to a fundamental mechanism within the psychedelic phenomenology requiring further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation